A Purposelless Effort: European Community and Croatian Serbs (Review of Croatian History, 2020)
In this paper, the authors analyses the relation of international community (European Community) to minority legislation of Republic of Croatia in 1991-1992. In concrete, establishing beyond dispute and evaluating the reasons why the Yugoslavia Peace Conference or special institution which European Community formed in order to find a peaceful solution of the conflict, pressed Zagreb strongly to make deep changes of minority legislation. Special attention is given to the Conference's fixation on special status or regional political autonomy for the territories of Republic of Croatia with Serbian majority.